Compliance Level Analysis of Announcement of General Procurement Plan in Indonesia - Darmawan Darmawan (Fakultas Ekonomi, Universitas Bangka Belitung, 2022)
The purpose of this study is to analyze the Compliance Level of the Public Procurement Plan Announcement in Indonesia. The observation period for this study was carried out for three years and for all Ministry / Agencies / Regional Government. The test was conducted to determine the effect of Value of Procurement, Way of Implementation, Type of Procurement, and Provider Selection Method on the level of compliance in announcing the General Procurement Plan. The level of compliance with the announcement of the General Procurement Plan was mostly influenced by the value of the procurement contract. It was also found that the number of procurement packages in a self-managed manner had a significant negative effect on the level of compliance. In the type of procurement, it was found that the value of the procurement packages had a greater influence on the number of packages. It was also found that the value of the consultant procurement package had a negative effect on the compliance level of the General Procurement Plan announcement. In the provider selection method, it was found that the value of the procurement packages had a greater influence on the number of procurement packages. In general, it is found that the variable value of the procurement packages significantly affects the level of compliance more than the number of procurement packages. The results of this research indicate the need for greater attention to the involvement of Small and medium enterprises and domestic production content in procurement. This is the first research effort to understand the success of the general procurement plan in Indonesia.